Last Insurer Standing: Accounting for Policyholder Settlements in an "All Sums" World. Issue 3 (3rd July 2019) - Martin, Craig; Scarbrough, Brian; Gillett, Gabriel; Rosoff, Katherine
Abstract: In 2016, New York became the latest state to interpret insurance policies with prior insurance or non-cumulation of liability clauses as permitting a policyholder to recover damages under "all sums" for long-tail liabilities, including environmental liabilities. But two major questions were left unanswered in New York, as in many other states, when a policyholder seeks all sums recovery from a non-settled insurer after the policyholder settles with other insurers: first, how to account for a policyholder's prior settlements—through set-off, contribution, or both. Second, how to calculate any set-off or contribution—should it be pro tanto, pro rata, or something else. This article examines the arguments on both sides of these issues and looks ahead to how courts may resolve these questions going forward.